Ennanga harp songs of Buganda: Temutewo Mukasa's "gganga alula" - Cooke, Andrew; Micklem, James (International Library of African Music, 1999)
For generations up until 1966, the Kabakas (kings) of Buganda in Uganda employed up to fifty musicians to entertain at the palace each day. During the time of Muteesa II, separate ensembles of flutes, trumpets, strings, tuned drums and xylophones played twice daily in the royal enclosure for the Kabaka (P. Cooke 1996). Perhaps the most privileged musician was the omulanga (royal harpist), who was the only musician allowed to enter the inner chambers of the palace. Ganda harpists of the past were renowned for their skill and their ability in composing new songs. Much of the repertory performed by the royal musicians is said to have been composed by harpists. Fortunately, Klaus Wachsmann and Hugh Tracey recorded the last great Ganda harpist, Temutewo Mukasa, in the 1940s and 1950s.
Keywords: African Music